Improving PGSD Students' Digital Literacy Through Interactive Multimedia-Based PBL - Susanti, Evi; Hikmat, Ade; Syafi'i, Imam (Institut Keguruan dan Ilmu Pendidikan Siliwangi, 2024)
This research is motivated by the lack of students' ability in digital literacy, and students are less active in learning. This study aims to determine the improvement of literacy skills and student constraints in using interactive multimedia-based problem-based learning models. The research method used is a mixed method with a sequential explanatory design. The subjects in this study were 36 PGSD studentsat a private university in Cimahi city. The data collection process was obtained from test questions, and student response questionnaires. The data collection techniques used are tests, interviews and observations. Data analysis is carried out with a quantitative approach, namely the t-test and a qualitative approach by coding and reducing data. The results showed that using the interactive multimedia-based problem- based learning model obtained an n-gain analysis of 76% with an effective category, and had an effect on the acquisition of students' average scores from the pretest and posttest process which initially amounted to 67 to 88.5. This shows that the interactive multimedia- based problem-based learning model can improve students' digital literacy. The findings are expected to contribute to university education to improve technological and interactive digital- based learning.